Gender role attitudes and work–family conflict: A multiple mediating model including moderated mediation analysis - Chen, Gongxing; Zhang, Jiamiao; Hu, Yingying; Gao, Yuan (Frontiers in Psychology, 2022)
This study aimed to explore the relationship between gender role attitudes, parental sacrifice, subjective well-being, and work-family conflict. Two models were tested using conditional process analysis for testing direct and indirect effects on a sample of 324 employees: A serial multiple mediation model, and the multiple mediation model including the moderating role of education level and subjective socioeconomic status. The results suggested that (1) gender role attitudes significantly and positively predicted work-family conflict. (2) Parental sacrifice and subjective well-being played multiple mediating roles between gender role attitudes and work-family conflict. (3) Education level moderated the relationship between gender role attitudes and parental sacrifice, as evidenced by the fact that low education level amplified the positive predictive effect of gender role attitudes on parental sacrifice. (4) Subjective socioeconomic status moderated the relationship between gender role attitudes and subjective well-being, suggesting that high subjective socioeconomic status amplified the negative predictive effect of gender role attitudes on subjective well-being. This work contributes to the understanding of the process underlying the relationship between gender role attitudes and work-family conflict, and to the literature reporting the possible moderated role of education level and subjective socioeconomic status on the influence outcomes of gender role attitudes. Practical implications are also discussed.